Tick-borne lymphadenopathy acquired in Serbia: Report of two cases - Gajinov Zorica; Roš Tatjana; Milana Ivkov-Simić; Gajić Branislava; Prćić Sonja; Matić Milan (Vojnosanitetski Pregled)
Introduction. Acronym tick-borne lymphoadenoathy (TIBOLA (Dermacentor-borne necrosis erythema and lymphoadenopathy – DEBONEL, scalp eschar associated with neck lymphoadenopathy – SENLAT) comprises clinical diagnosis of tick-borne symptoms of cervical or occipital lymphadenopathy with inoculation eschar at the site of tick bite on scalp. Since the first description, it was proved to be associated with several infectious agents, most frequently Rickettsia slovaca, or less often other spotted fever group Rickettsiae (Rickettsia raoulti and Rickettsia rioja), and gained an emerging infectious disease status in Europe. Dermacentor ticks serve as vectors and possible natural reservoir. The course is in most cases benign and infection is limited. Doxicycline is the recommended initial treatment, both for adult and most cases in children. Case report. Two subjects who acquired the desease caused by tick bites in Vojvodina region of Serbia are presented. Both patients are females. A tick was removed from the scalp, and several days later doxicycline treatment started because of the inflammatory symptoms of lymph node enlargement. Diagnostic eschar appeared in both patients during doxicycline treatment. After a switch to ciprofloxacine, inflammatory symptoms subsided, but the complete healing of scalp necrosis took longer than one month, with residual cicatricial alopecia. Conclusion. Although rare, it is necessary to include TIBOLA in a spectrum of epidemiologic risks in cases of tick bites.